2015
DOI: 10.1021/acs.joc.5b00523
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Cu(I)- and Cu(II)-Catalyzed Cyclization of o-Alkynylbenzaldehydes: The Solvent DMF and Oxidation State of Copper Affect the Reaction Mechanism

Abstract: A computational study with the BhandHLYP density functional is conducted to elucidate the mechanisms of Cu(I)- and Cu(II)-catalyzed reactions of o-alkynylbenzaldehydes with a nucleophile (MeOH). Our calculations suggest the following. (a) The use of CuCl as a catalyst deceases significantly the energy barrier and promotes intramolecular cyclization. (b) Solvent DMF is critical in the stepwise hydrogen-transport process involved in an intermolecular nucleophilic addition because it can greatly reduce the free e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…Similar effect of solvents has been found by Yamamoto, Xia and Li et al . Besides, the reactance MeOH also prompts the catalytic reactions as the proton‐shuttle reagent, which has been discovered in our previous theoretical studies. Interestingly, Li and co‐workers found that the OTf − ‐assisted 1,2‐H migration required the activation energy of only 9.6 kcal/mol, while the activation energy barrier was much higher (20.2 and 29.0 kcal/mol, respectively) for BF 4 − ‐ and SbF 6 − ‐assisted H‐shift process in the Au(PR 3 ) + ‐catalyzed cycloisomerization of bromoallenyl ketones.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Similar effect of solvents has been found by Yamamoto, Xia and Li et al . Besides, the reactance MeOH also prompts the catalytic reactions as the proton‐shuttle reagent, which has been discovered in our previous theoretical studies. Interestingly, Li and co‐workers found that the OTf − ‐assisted 1,2‐H migration required the activation energy of only 9.6 kcal/mol, while the activation energy barrier was much higher (20.2 and 29.0 kcal/mol, respectively) for BF 4 − ‐ and SbF 6 − ‐assisted H‐shift process in the Au(PR 3 ) + ‐catalyzed cycloisomerization of bromoallenyl ketones.…”
Section: Introductionmentioning
confidence: 66%
“…Yamamoto and co‐workers presented that solvent DMF could not only offer an appropriate catalytic medium for the synthesis of cyclic alkenyl ethers via intramolecular cyclization of o ‐Alkynylbenzaldehydes using Cu(I) salts as the catalysts, but also serve as a cocatalyst to directly participate in the reaction. In this reaction, our previous study showed that DMF molecule played the role of proton‐shuttle to assist proton shift from MeOH to carbon atom of substrate (2‐(1‐alkynyl)‐2‐alken‐1‐ones). Similar effect of solvents has been found by Yamamoto, Xia and Li et al .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this experimental phenomenon can be explained by the loose scan profile (see Figure S4 in Supporting Information). The method using the loose scan to explain the experimental results has been adopted successfully in the previous theoretical calculations . As shown in Figure S4, the energy curve is sharply rising in energy with the formation of O1‐C1 bond from 1a to in1’ , meaning that the intramolecular cyclization of O1 with C1 cannot be carried out without the participation of Au(I) catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…The geometric structures of all the intermediates and the transition states are calculated with the Becke three‐parameter hybrid functional (B3LYP) in the framework of density functional theory (DFT) . This computational method has been successfully applied in the mechanistic studies of transition‐metal‐catalyzed reactions . As a further test for the functionals CAM‐B3LYP, M06, BLYP, B3P86, B3PW91 and BHandHLYP are evaluated, and their calculation results are close to those of B3LYP (see Table S1 in Supporting Information).…”
Section: Computation Methodsmentioning
confidence: 97%
See 1 more Smart Citation